What would an informant tell me after reading my paper?: on the theoretical significance of ethical commitment and political transparency in symmetrical practice of studying religion(s) - Fujda, Milan (Religio, 2015)
This article introduces the methodological principle of symmetry as developed in science and technology studies (STS). However simple in its formulation, this principle is unexpectedly complex in practice and has far-reaching consequences. Adherence to the principle of symmetry in the study of religion(s) is one promising avenue through which practical solutions to many theoretical and methodological problems may be formulated in response to postmodern and postcolonial critique of the study of religion(s) as well as of the modern scientific practice in general. The aim of this article is to demonstrate the promises of the symmetrical approach, the ways of its practical enactment, the complications of this enactment, and some solutions for these complications. The arguments and demonstrations provided here show that: (1) demarcating the research field of the study of religion(s) through the concept "religion" in itself creates asymmetries which contradict the aims of the discipline as an objective empirical and theoretical study; (2) the practical enactment of the principle of symmetry demands taking important ethical and political decisions in order to prepare the practical conditions for research and analysis, analogical to the practical conditions actively fostering democratic negotiation and handling inequalities through affirmative action; (3) making these decisions and maintaining these conditions is necessary in order to achieve theoretical objectivity and build good and transparent theories; and (4) being faithful to these decisions during the process of data analysis is extremely complicated and can only be more or less successfully achieved on the basis of (a) high degree of ethical commitments towards the participants in research which empower them politically in relation to the researcher and the research itself, and (b) by analysing the process of data collection and analysis in exactly the same way (i.e. symmetrically) as the activities of all other actors engaged in the research. In this sense modernist ideas concerning moral and political disengagement as the condition for neutrality, objectivity and truth are reversed with reference to postcolonial criticism and show how proclaimed neutrality, objectivity and truth justifications are based on and foster power domination, suffering and exploitation of the marginalized.